Effect of pelleting process on proximate analysis of total mixed rations for lactating dairy goats - Siti Nursolehah Rozainal (2022)
Lactating dairy goat performance can be improved by feeding a total mixed ration (TMR), as it provides a nutritionally balanced ration to meet the energy and protein needs for optimum efficiency. However, the use of TMR needs to be monitored daily due to high moisture ingredients. In order to prevent the overheated and spoiled condition, TMR was pelletized. Pelleting process may affect TMR quality and feed value. Therefore, this study aims to evaluate the effect of pelleting process on the proximate and mineral compositions of TMR for lactating dairy goats. The TMR was formulated using local ingredients which consists of palm kernel cake (PKC), PFAD, molasses, vitamin/mineral premix, salt, Napier grass, soy hull, soybean meal and sodium bicarbonate as the binding agent. Two different forms of TMR were investigated; conventional TMR and pelleted TMR. The formulated TMR pellet was isocaloric and isonitrogenous. The proximate analysis of TMR pellet has different value results for before and after pelletizing. This is because the TMR was undergo heating process during pelletizing. There were some changes in the proximate of the TMR. Between mixture and pelleted TMR, there is no significant difference (p>0.05) in CP, moisture, ash, DM, and EE, but have significant difference (p<0.05) in CF. The current finding may help in improving the quality of the pellets on shelf for a longer period and reduces the feed cost.